2006
DOI: 10.1002/mrd.20392
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of embryonic stem-like cells from canine blastocysts

Abstract: Embryonic stem (ES) cells are pluripotent cells with the capacity to generate any type of cell. Here we describe the isolation of ES-like cells from canine blastocysts. Canine embryos were collected from beagle bitches at day 11-16 of first estrus. A total of 80 normal embryos were obtained from 15 dogs. Of the embryos, 13 were at the morulae stage, 39 at the blastocyst stage, and 28 at the hatched blastocyst stage. The inside of morulae or inner cell masses (ICMs) of blastocysts were isolated mechanically, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
59
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 39 publications
5
59
1
4
Order By: Relevance
“…Sequencing confirmed that the obtained polymerase chain reaction (PCR) products correspond to canine sequences. Furthermore, in agreement with the report by Hatoya et al [9], the canine ES-like cells showed expression of SSEA-1 but were negative for SSEA-4 (data not shown).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Sequencing confirmed that the obtained polymerase chain reaction (PCR) products correspond to canine sequences. Furthermore, in agreement with the report by Hatoya et al [9], the canine ES-like cells showed expression of SSEA-1 but were negative for SSEA-4 (data not shown).…”
supporting
confidence: 92%
“…In a recent report, Hatoya and colleagues [9] describe the isolation of two ES-like cell lines from canine blastocysts. The cell lines were shown to exhibit characteristic ES-like morphology and expression of pluripotency markers.…”
mentioning
confidence: 99%
“…In the case of antibodies specific for SSEA-1, also known as CD15, which is expressed on human granulocytes as well as human ES cells, there was no specific labeling of dog granulocytes or ES cells (data not shown). This differed from the two previous reports on dog ES cells [15,16]; however, in the first study, no specificity controls for staining were included, and in the second, the data were not shown and the methods were not discussed.…”
Section: Characterization Of Fhdo-7 (Passage Number >20)mentioning
confidence: 71%
“…Corresponding results were reported by [30], in which cat ES-like cells expressed the "stemness" transcription factors and the levels of expression of OCT-4, NANOG and C-MYC were reduced in cat ES-like colonies as compared to that seen in blastocysts. In other study, expression of transcription factors like Oct 4 and Nanog were used as molecular markers for ES cells in various species [16,17,[41][42][43]. Moreover, when undifferentiated primary colonies were analyzed for the expression of pluripotent transcription factors, Gómez et al [30] found that OCT-4 was down regulated regardless of the expression of NANOG.…”
Section: Discussionmentioning
confidence: 99%